Implementation of Sustainable Leadership in Higher Education in Supporting Education for Sustainable Development (ESD) - Sofiyanti, Neneng; Marampa, Adriana Madya (Westscience Press, 2025)
This study examines the role of sustainable leadership in higher education in supporting education for sustainable development (ESD) and innovation within Indonesian universities. Using a quantitative research design, data were collected from 175 respondents through a structured questionnaire employing a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results reveal that sustainable leadership has a significant positive effect on both ESD and innovation. Moreover, ESD itself exerts a strong positive influence on innovation and mediates the relationship between sustainable leadership and innovation. The model demonstrates substantial explanatory power, with R² values of 0.56 for ESD and 0.63 for innovation, and good predictive relevance (Q² > 0). These findings highlight the importance of embedding sustainability principles in leadership practices and integrating ESD into academic programs, research, and institutional culture. For Indonesian higher education, the results suggest that innovation is best achieved when leadership practices are grounded in sustainability values, thus enabling universities to contribute more effectively to sustainable development and national innovation goals.